Online Shopping Behaviours in an Emerging Economy of Eastern Cape, South Africa - Townes, Juliet; Pike-Bowles, Angela (Contemporary Issues of Business and Management: The Proceedings of the \(10^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
E-commerce has proliferated over the last decade due to its ease and convenience. This has resulted in a new era of shopping, where society now uses online shopping platforms on electronic devices such as cell phones, tablets, laptops, and computers to make purchases. Although e-commerce research has increased over the last ten years, there is still insufficient attention to online shopping in emerging economies. This study contributes to the body of knowledge and the call for studies in this area within developing economies. The study examined the characteristics of university students in South Africa and their perceptions of online shopping behaviour. The perception variables measured for online shopping behaviour were functionality, risk, convenience, decision influence and security. The focus locale was the Eastern Cape, South Africa, an emerging economy. The study followed a quantitative investigation employing a questionnaire as the selected research instrument. A total of 219 university students participated in the investigation. Furthermore, the analytical approach entailed a statistical analysis using SPSS. The study revealed that university students prefer online shopping using their cell phones, with fashion being the most popular online product category purchased. The study further explored that university students in an emerging economy are influenced by online shopping platforms’ functionality, security, and convenience facets. University students are reluctant to shop online if such features are not apparent on the online shopping platform. Based on this study's findings, practical and theoretical contributions to the academic domain have implications for business owners trading online.